A brief psychological intervention for chronic pain in primary care: Examining long‐term effects from a pilot randomized clinical trial. Issue 6 (14th June 2022) - Miller‐Matero, Lisa R.; Gavrilova, Lyubov; Hecht, Leah M.; Autio, Kirsti; Tobin, Erin T.; Braciszewski, Jordan M.; Maye, Melissa; Felton, Julia W.; Ahmedani, Brian K.
Abstract: Background: Despite the existence of evidence‐based psychological interventions for pain management, there are barriers that interfere with treatment engagement. A brief intervention integrated into primary care reduced barriers and showed promising benefits from pre‐ to post‐intervention. However, it is unknown whether a brief intervention can provide long‐term effects. The purpose of this study was to examine whether a brief psychological intervention offered benefits in pain severity, pain interference, pain catastrophizing, and depressive symptoms at 1‐ and 6‐month follow‐ups. Methods: The majority of participants who enrolled in a pilot randomized clinical trial of a 5‐session psychological intervention for chronic pain in primary care completed the 1‐month ( n = 54; 90%) and 6‐month follow‐ups ( n = 50; 83.3%). Participants completed measures of pain severity, pain interference, pain catastrophizing, and depressive symptoms. Results: From baseline to the 6‐month follow‐up, those in the intervention group had significantly better outcomes for pain severity ( p = 0.01) and pain catastrophizing ( p = 0.003) compared with the control group. There were no significant differences between the intervention and control groups for pain interference and depression. The percentage of patients in the intervention experiencing clinically significant improvement across all outcomes was higher than the control group. Conclusions: Findings suggest that a brief psychological intervention for chronic pain in primary care may offer longer‐term benefits similar to that of lengthier interventions. Future studies should examine this through a randomized clinical trial with a larger sample size.